OWE-004 Iscan OE improves detection of early barretts oesophagus associated neoplasia in trainee and expert endoscopists. (8th June 2018) - Everson, Martin; Bisschops, Raf; Wani, Sachin; Graham, David; Banks, Matthew; Magee, Cormac; Alzoubaid, Durayd; Omer Ahmad, O; Ortiz-Fernandez-Sordo, Jacobo; Lovat, Laurence; Sweis, Rami; Esteban, Jose; et al.
Abstract : Introduction: The Seattle protocol for BE surveillance samples a small proportion of the mucosal surface area – risking a high miss rate of early neoplastic lesions. We assessed if the new iScan Optical Enhancement system (OE, Pentax) improves the detection of early BE associated neoplasia compared to high definition white light endoscopy (HD-WLE) in both expert and trainee endoscopists. Such a system may both improve early neoplasia detection and reduce the need for random biopsies. Methods: Patients undergoing endoscopic BE surveillance from Jan 2016-Nov 2017 were recruited from 3 international referral centres. Matched still images in both HD-WLE and iScan OE were obtained from HD videos of endoscopic examinations. Two experts, unblinded to the videos and histology, delineated known neoplasia – forming a consensus 'gold standard'. 7 expert and 7 trainee endoscopists marked one position per image where they would expect a target biopsy to identify dysplastic tissue. Sensitivity, specificity and accuracy were calculated. Improvements in dysplasia detection in HD-WLE vs OE and interobserver agreement (IA) were assessed using McNemars test and Krippendorf's alpha respectively. Results: Accuracy of neoplasia detection improved in all trainees using OE vs WLE (pooled 76% vs 63%) and in 6 experts (pooled 86% vs 78%). OE improved detection sensitivity compared to WLE in 6 trainees (pooled: 81% [62–94%] vs 71% [50–86%]) and 5 experts (pooled: 79.4% [62–92.5%] vs 65% [52–82%]). Specificity improved in 6 trainees using OE vs WLE (pooled: 71% [50–84%] vs 55% [40–91%]) and in 5 experts (pooled: 92% [78.5–100%] vs 90.3% [55.9–99%]) Trainees and experts made significantly more correct diagnoses using OE (pooled: 689 vs 570, p≤0.001, pooled: 789 vs 699 p≤0.001 respectively). IA in both groups improved using OE and was fair and moderate for each group respectively (trainees OE vs WLE: 0.39 vs 0.23, experts OE vs WLE: 0.46 vs 0.39). Conclusion: iScan OE improves the diagnostic accuracy of expert and trainee endoscopists performing BE surveillance. OE significantly improves sensitivity and specificity of neoplasia detection. It does not meet the Preservation and Incorporation of Valuable Endoscopic Innovations guidelines (PIVI) but shows promise for use in the training environment or in a secondary care setting where caseloads of early BE neoplasia may be lower.